Exploring readiness for successful outcome of business intelligent implementation: a case study of RMCD - Ismail, Shahrizul (2020)
Business Intelligence (BI) aim is to supports users in taking the right decision to access the right data in the right time which provided a competitive advantage for businesses to use. In the sense of supporting decision-making, BI in the public sector context act as the design and integration of integrated operations, as well as support and database applications that provide access to business data for the public sector. As RMCD is one of Malaysia's major public organizations, it is critical for RMCD to be well prepared to introduce BI so that the implementation process can be done efficiently and effectively. This study focuses on assessing readiness elements of critical success factors for Business Intelligence adoption in Royal Malaysian Customs and how these CSF elements contribute to successful BI implementation. This research uses a qualitative methodology. A qualitative case study has been conducted to thoroughly analyse the readiness assessment that has been applied to Royal Malaysian Customs (RMCD) as one of the biggest and important public sectors in Malaysia. The findings of the study found that readiness elements of CSF of BI in RMCD are divided under three categories which are organization, process and technological. In organization, clear vision, continuous management support and strategic alignment are mention by the participants as the important readiness elements of CSF. As for process, the resource allocation, risk assessment and beurocracy are said as the vital readiness elements in this category. In technological, IT infrastructure and data quality are crucial readiness elements in CSF. These elements contribute to successful BI implementation as it acts as effective planning, problem solving and acceptance testing. The implications of the finding as well as recommendation for future research are also presented in this study.